Análise da integração da cadeia da construção civil na região metropolitana de Fortaleza - Araújo, Marcela Costa (2015)
The building is a fairly unique industry. It is a very complex chain of great importance given the effects that this has on the economy and consumption of natural resources. In 2010 came into force on Modular Coordination standard that seeks to reduce costs through standardization and waste in this industry. The supply chain of construction needs to improve their integration in order to become more competitive at the same time it needs to adapt to the constant changes in the external environment, such as market regulations and reducing environmental impact. This research analyzes and seeks to understand the existing barriers to the development of the Construction chain in the metropolitan area of Fortaleza, considering aspects of standardization and environmental legislation. This research deals with the production flows in factory of concrete blocks, ceramic, construction sites and their impacts on the application of modular coordination and evaluates the expectations regarding the use of modular coordination by the actors involved, providing guidelines for the modeling of the construction chain civil. The results indicate that the modular coordination is not yet known and applied by companies despite the existence of Modular Coordination Standard since 2010 and that this lack harms the development and performance of the chain, which may negatively impact on the environment.